2001
DOI: 10.1136/bjo.85.11.1332
|View full text |Cite
|
Sign up to set email alerts
|

The Rotterdam AMblyopia Screening Effectiveness Study (RAMSES): compliance and predictive value in the first 2 years

Abstract: Background-RAMSES is a 7 year follow up study, aiming at the evaluation of the eVectiveness and the eYciency of screening for amblyopia. In this first report, concerning the first 2 years of life, the compliance with the prevention programme and the positive predictive value (PPV) of the screening tests used, are presented. Methods-All results of the standardised screening test for strabismus, applied by child healthcare physicians, within a birth cohort of 4072 Rotterdam children at the age of 9, 14, and 24 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
1
12
0
3
Order By: Relevance
“…14 In the Netherlands, 97% of all children of this age attend the child health screening programme, which is government paid. All Child Health Care centres and municipal health service locations in the Rotterdam region participated in the study.…”
mentioning
confidence: 99%
“…14 In the Netherlands, 97% of all children of this age attend the child health screening programme, which is government paid. All Child Health Care centres and municipal health service locations in the Rotterdam region participated in the study.…”
mentioning
confidence: 99%
“…Juttmann, 82 on behalf of the Rotterdam Amblyopia Screening Effectiveness Study (RAMSES) steering committee, reported on the compliance with vision screening and the PPV of the screening tests used. In this programme children were screened during the first 2 years of life by healthcare physicians.…”
mentioning
confidence: 99%
“…Compliance with a referral after a positive screening test, however, may influence an amblyopia outcome as well. [12][13][14] Williamson and colleagues 15 showed that high rates of default in terms of vision screening appointments, particularly in geographical areas of lower socioeconomic classification, have hampered the attempts at reducing the incidence of insufficiently treated amblyopia. Early results of a large birth-cohort study on vision screening showed that approximately one third of the children had not been successfully referred after a positive screening test.…”
mentioning
confidence: 98%
“…Early results of a large birth-cohort study on vision screening showed that approximately one third of the children had not been successfully referred after a positive screening test. 6,14 In the current study, we investigated noncompliance after a positive vision-screening examination to determine reasons for unsuccessful referral.…”
mentioning
confidence: 99%